RESPONSE OF EGGPLANT PLANTS TO BIOSTIMULATORES AND SHADING - & AL-Baity, Abu-Alaees (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was carried out in the vegetable field of Horticulture Department and Landscape Gardening, College of Agriculture, Abu-Ghraib In the spring season 2014 to study the Response of Eggplant Plants to Biostimulators and Shading, to study of Two factors, the first factor represent two treatments, first is shading with plastic nets (50% light) and the second without shading, each of these treatments contained three replicates and distributed randomly Treatments were(Without adding, Endospor Dry Mix, Biohealth, Amino Alexin, interacion between Endospor Dry Mix and Biohealth interaction between Endospor Dry Mix and Amino Alexin interaction between Biohealth and Amino Alexin triple interaction between Endospor Dry Mix and Biohealth and Amino Alexin and symbolized by (Control, A, B, O, AB, AO, BO and ABO). The experiment carried out within (Nested Design), the Results and analyzed compared with the averages according to less significant difference test ( LSD) at the probability level of 5%.The results can be summarized by. The treatment A gave a significantly higher values in the leaf area are (1299 dm2.plant-1) and the length of the secondary root is (35.08 mm) the roots surface area is (1300 cm2) and total yield is (92.10 ton.ha-1) while the treatment BO give a significantly higher values in the number of fruitful branches are (12.83 fruitful branch.plant-1) and the diameter of the main root is (4.93 mm). And the treatment AO give a significantly higher values in the concentration of total chlorophyll pigment in the leaves (543.5 mg.100g-1 fresh weight). And the treatment ABO give a significantly higher values in the fruit weight is (177.3 g) and the concentration of Fe in the leaves (255.2 mg.kg-1 dry matter) and Zn (83.50 mg.kg-1 dry matter) and Mg (0.186 mg.kg-1 dry matter). The shading treatment a significantly higher values in the concentration of Fe in the leaves (237.0 mg.kg-1 dry matter) and Zn (71.67 mg.kg-1 dry matter). The number of fruit branches are (10.83 fruitful branch.plant-1) and the leaf area are (1353 dm2.plant-1), and the concentration of chlorophyll pigment in the leaves is (493.6 mg.100g-1 fresh weight) and the diameter of the main root way (4.29 mm) and the length of secondary root is (31.58cm) and the surface area of the roots is (1190 cm) and the weight of the fruit is (169.6 g) and the total yield is (76.05 ton.ha-1).The interaction between treatment A and shading significantly in the number of fruitful branches is (15 fruitful branch.plant-1) and the length of secondary root (39.33 cm) and the total yield is (98.03 ton.ha-1). And the superiority of interaction between the treatment AO and the shading significantly in the leaf area in were (1645 dm2.plant-1) and the concentration of chlorophyll pigment in the leaves way (575.0 mg.100 g-1 fresh weight). While the interaction between the treatment BO and shading in the surface area of the roots way (1336 cm2). And the interaction between the treatment ABO and shading give a significantly value in the fruit weight is (184.6 g) and the concentration of Fe in the leaves (261.0 mg.kg-1 dry matter), and Zn (86.00 mg.kg-1 dry matter) And the interaction between the treatment BO and without shading gave a significantly value in diameter main root way (5.37 mm).